Комплексный контроль санитарно-гигиенического состояния рабочей зоны - Поперека, Екатерина Дмитриевна; Костенко, Виталий Леонидович (НТУ "ХПИ", 2015)
В работе проведены исследования по комплексному контролю санитарно-гигиенического состояния рабочей зоны. Особое внимание уделено созданию устройства контроля, позволяющего в автоматическом режиме исследовать нормированные параметры, а также ускорить процесс измерения. Для этого проведено исследование выбранных комплектующих компонентов устройства, датчиков и их измерительных цепей с целью оптимизации контроля. Приведены результаты комплексного контроля санитарно-гигиенического состояния рабочей зоны.

The paper conducted research on integrated control of sanitary conditions of the working area. Particular attention is paid to the creation of a control device can automatically explore the normalized parameters, as well as accelerate the process of measurement. For a study of selected components of the device components, sensors and measurement circuits in order to optimize control. The results of the integrated control of sanitary and hygienic state of the working area. The analysis conducted in this paper studies the complex control hygienic factors using the layout of the developed device in industrial conditions possible to estimate the complex refractive deviation hygiene at controlled workplaces. These results confirm the prospects for comprehensive monitoring of sanitary and hygienic state of the working area and can be used to ensure safe working conditions.
Integrated control of sanitary-hygienic condition of the working area
Keywords: исследования; средства измерения; датчики; нормированные параметры; research unit; measuring sensors; normalized parameters